Estrategias de marketing en la Empresa Fríos Repuesto V. M. en la ciudad de Babahoyo periodo 2021 - Valero Mosquera, Karina Lorena (2022)
The case study entitled "Marketing strategies in the company Frios Repuesto V.M in the city of Babahoyo period 2021”, whose main commercial activity is determined through the commercialization of spare parts such as washing machines, air conditioning, compressors, trainers, etc. It has as a general objective; Analyze the marketing strategies within the company, evaluating the customer loyalty process in the business, the hypothetical-deductive method was applied, since it will help to investigate bases from facts and in this way generate adequate comments for the development of this case study, the techniques that are implemented were the following: the survey and interview technique, concluding the following: The study is framed under the guidelines established by the Technical University of Babahoyo, with which it has been tried to identify and analyze the problematic factors originated in the company Frios Repuesto V.M, which has been identified as having a deficit in the implementation of current marketing strategies, causing customer dissatisfaction due to the little information presented by the commercial, which has generated an economic gap and little demand for the digital medium used, which the existing merchandise has been kept in stock for a long time, due to poor administrative management in the marketing area. These and other negative peculiarities that affect the company are detailed later in the development of this study.